Bonding with natural fibres - Md. Tahir, Paridah (Universiti Putra Malaysia Press, 2013)
The earliest evidence of humans using fibres is the discovery of wool and dyed flax fibres found in a cave in the Republic of Georgia more than 30,000 years ago. It all started with the use of natural fibres in composite materials. Clay was reinforced by straw to build walls in ancient Egypt about 3,000 years ago. The famous Great Wall of China was made using a combination of clay and rice flour reinforced with straw. Now composites dominate our lives in many ways – automotives, buildings, sports, defence, aerospace, and the list continues. With its apparent endless uses, natural fibres are indeed phenomenal and eternal. Natural fibres are bio-based fibres, i.e.,fibres of vegetable or animal origin. Between the two, the former which is the focus of this book, has received tremendous attention for decades and the interest are still growing strongly. Natural fibres are sometimes referred to as plant fibres. These field crops are grown for their fibres, which are traditionally used to make paper, cloth , or rope, products that are responsible for its continued existence. While wood comes from forest trees that requires many years (>15 years) to mature, the non-woods mature between 3-10 years, and fibre crops are generally harvestable after a single growing season (5-6 months). In specific circumstances, fibre crops can be superior to single wood fibre in terms of technical performance, environmental impact and cost. Biomass is another source of fibres that can be derived from plants, either from forest trees or field crops, normally in the form of residues. It is usually associated with energy production and bio- refinery. In this book, the term “natural fibres” is used to describe fibres that are obtained from wood, non-wood, plant fibres and biomass. All natural fibres are chemically made up of cellulose, hemicellulose and lignin which are aligned in crystalline and amorphous regions in the form of microfibrils. Aggregates of microfibrils make up a fibre. These fibres are arranged in different manner depending on the type of plant. Some examples of wood are pines, spruce, oak, beech, hemlock (temperate woods), meranti, keruing, chengal, rubberwood, (tropical woods). Examples of non- woods are bamboo, rattan and all types of palms. Plant fibres are represented by many types depending on where the fibres are taken, e.g., bast fibres - the fibres that come from the phloem tissue of the plant, as exemplified by jute, kenaf, ramie, flax, and hemp. Other fibre crop fibres are from seed padding, such as coir, leaf fibre, such as those of pineapple, abaca, sisal, henequen, or from other parts of the plant. All plant fibre residues from the forests, plantations/ estates and processing mills are regarded as plant biomass. In recent years, materials scientists and engineers have begun exploring further uses of natural fibres through composite materials. This book reviews the basic properties of some natural fibres particularly those found in Malaysia, and highlights issues in bonding with polymer, surface wettability, buffering capacity and their influence on composite performance.